Poor performance of psoas muscle index for identification of patients with higher waitlist mortality risk in cirrhosis. Issue 6 (29th September 2018) - Ebadi, Maryam; Wang, Connie W.; Lai, Jennifer C.; Dasarathy, Srinivasan; Kappus, Matthew R.; Dunn, Michael A.; Carey, Elizabeth J.; Montano‐Loza, Aldo J.; ,
Abstract: Background: Sarcopenia, characterized by low muscle mass, associates with mortality in patients with cirrhosis. Skeletal muscle area in a single computed tomography image at the level of the third lumbar vertebrate (L3) is a valid representative of whole body muscle mass. Controversy remains regarding applicability of psoas muscle to identify patients at greater risk of mortality. We aimed to determine psoas muscle index (PMI) association with skeletal muscle index (SMI) and to evaluate the capacity of PMI to predict liver transplant waitlist mortality. Methods: We evaluated listed adult patients with cirrhosis from 2012 to 2013 at four North American liver transplant centres. From L3 computed tomography images within 3 months of listing, we determined SMI and PMI expressed by cm 2 /m 2 . Low SMI was defined as SMI <39 cm 2 /m 2 in women and <50 cm 2 /m 2 in men as published by us earlier. Cut‐offs for PMI to predict mortality were established using a receiver‐operating characteristic analysis. Mortality predictors were determined using competing‐risk analysis with reported results as subdistribution hazard ratios (sHRs). Results: Of 353 waitlist candidates, 68% were men, mean age 56 ± 9 years, and Model for End‐stage Liver Disease of 16 ± 8 points. Low SMI was present more frequently in men than women (51 vs. 36%, P  = 0.02). Moderately strong correlation between SMI and PMI was observed ( r  > 0.7, P  < 0.001). Low PMI (males < 5.1 cm 2 /m 2 ; females < 4.3 cm 2 /m 2 ) yielded poor and moderate concordance with low SMI in men and women, respectively (Kappa coefficient 0.31 and 0.63). SMI (39 ± 9 vs. 43 ± 7 cm 2 /m 2 ; P  = 0.009) and PMI (4.4 ± 1.3 vs. 5.2 ± 1.1 cm 2 /m 2 ; P  = 0.001) were lower in women who died and/or were delisted (compared with non‐deceased patients) whereas men who died and/or were delisted had only lower SMI (47 ± 7 vs. 51 ± 9 cm 2 /m 2 ; P  = 0.003), but not PMI compared with non‐deceased patients. In women, both SMI (sHR 0.94, P  = 0.048) and PMI (sHR 0.58, P  = 0.002) were predictors of mortality, while in men, SMI was significant (sHR 0.95, P  = 0.001) and PMI showed a trend to be (sHR 0.85, P  = 0.09) associated with mortality. Overall, 104 patients (29%) were misclassified between SMI and PMI categories. Using PMI cut‐offs, 66% and 28% of low SMI men and women, who have a higher risk of mortality, were incorrectly classified as low risk. Conclusions: Skeletal muscle index is a more complete and robust measurement than PMI, especially in men with cirrhosis. Low PMI identifies an incomplete subset of patients at increased risk of mortality indicated by low SMI. Given the poor performance of PMI, SMI should not be substituted by PMI.